HIV-1 virological remission lasting more than 12 years after interruption of early antiretroviral therapy in a perinatally infected teenager enrolled in the French ANRS EPF-CO10 paediatric cohort: a case report. Issue 1 (January 2016) - Frange, Pierre; Faye, Albert; Avettand-Fenoël, Véronique; Bellaton, Erianna; Descamps, Diane; Angin, Mathieu; David, Annie; Caillat-Zucman, Sophie; Peytavin, Gilles; Dollfus, Catherine; Le Chenadec, Jerome; Warszawski, Josiane; et al.
Summary: Background: Durable HIV-1 remission after interruption of combined antiretroviral therapy (ART) has been reported in some adults who started treatment during primary infection; however, whether long-term remission in vertically infected children is possible was unknown. We report a case of a young adult perinatally infected with HIV-1 with viral remission despite long-term treatment interruption. Methods: The patient was identified in the ANRS EPF-CO10 paediatric cohort among 100 children infected with HIV perinatally who started ART before 6 months of age. HIV RNA viral load and CD4 cell counts were monitored from birth. Ultrasensitive HIV RNA, peripheral blood mononuclear cell (PBMC)-associated HIV DNA, HIV-specific T-cell responses (ie, production of cytokines and capacity to suppress HIV infection), reactivation of the CD4 cell reservoir (measured by p24 ELISA and HIV RNA in supernatants upon phytohaemagglutinin activation of purified CD4 cells), and plasma concentrations of antiretroviral drugs were assessed after 10 years of documented control off therapy. Findings: The infant was born in 1996 to a woman with uncontrolled HIV-1 viraemia and received zidovudine-based prophylaxis for 6 weeks. HIV RNA and DNA were not detected 3 days and 14 days after birth. HIV DNA was detected at 4 weeks of age. HIV RNA reached 2·17× 10 6 copies per mL at 3 months of age and ART was started. HIV RNA was undetectable 1 month later. ART was discontinued by the family at some point between 5·8 and 6·8 years of age. HIV RNA was undetectable at 6·8 years of age and ART was not resumed. HIV RNA has remained below 50 copies per mL and CD4 cell counts stable through to 18·6 years of age. After 11·5 years of control off treatment, HIV RNA was below 4 copies per mL and HIV DNA was 2·2 log10 copies per 10 6 PBMCs. The HLA genotype showed homozygosity at several loci (A*2301-, B*1503/4101, C*0210/0802, DRB1*1101-, and DQB1*0602-). HIV-specific CD8 T-cell responses and T-cell activation were weak. Interpretation: Findings from this case suggest that long-term HIV-1 remission is possible in perinatally infected children who receive treatment early, with characteristics similar to those reported in adult HIV post-treatment controllers. Further studies are needed to understand the mechanisms associated with HIV remission and whether early treatment of infected children might favour the conditions needed to achieve HIV control after treatment discontinuation. Funding: Agence de recherche ANRS (France Recherche Nord & Sud Sida-HIV Hépatites).